2022
DOI: 10.2176/jns-nmc.2022-0077
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Planning Using Three-dimensional Printing for Full-endoscopic Spine Surgery: A Technical Note

Abstract: Transforaminal full-endoscopic spine surgery (TF-FESS) is a novel minimally invasive spine surgery that requires only an 8-mm skin incision and causes minimal damage to the paravertebral muscles. To perform TF-FESS safely and efficiently, preoperative planning is quite important as the intervention requires anatomical understanding and high technical skills. Recently, three-dimensional (3D) printing has become a useful tool in various surgeries, and several studies have addressed its efficacy; however, there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…We consider that surgical training using a 3D printer can compensate for these shortcomings. A 3D-printed model that was useful for surgical simulation has previously been reported 9 . In addition, 3D-printed models can be used as disease models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We consider that surgical training using a 3D printer can compensate for these shortcomings. A 3D-printed model that was useful for surgical simulation has previously been reported 9 . In addition, 3D-printed models can be used as disease models.…”
Section: Discussionmentioning
confidence: 99%
“…3D-printed models are also inexpensive, although the price varies depending on the type and amount of material used. Okada et al 9 reported a cost of less than USD 10 per patient to produce a 3D-printed model. In this study, the cost of creating a 3D-printed model was USD 10-15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation